The obstacle race: the fortunes of women painters and their work - Greer, Germaine (Farrar, Straus, Giroux, 1979)
If men and women are equally capable of genius, why have there been no female artists of the stature of Leonardo, Titian or Poussin? In seeking to answer this question, Germaine Greer introduces us to major but underestimated figures in the history of Western painting–Angelica Kauffmann, Natalia Goncharova, Suzanne Valadon, Berthe Morisot, Kathe Köllwitz–and produces a brilliantly incisive and richly illustrated study. She explains the obstacles as both external and surmountable and internal and insurmountable in the race for achievement.
Section: 373 pages
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; arts; cours; discipline; discours dominant; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; périodes historiques; régions; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théorie de l'art

Question de différence - Guillaumin, Colette (Questions Féministes, 1979)
La « différence » est une relation entre hommes et femmes qui assigne à l'un des groupes, celui des femmes, des obligations matérielles envers l'autre groupe ; imposées par des signes dans le corps (motricité entravée, vête-ments, usage de l'espace et du temps) elles nous à intérioriser la soumission et la disponibilité. La différence n'est ni « naturelle » ni bonne en soi. Conséquence banale de ce qui nous est imposé socialement, elle est l'expression de la relation de pouvoir entre hommes et femmes, Revendiquer un « droit à la différence » est acte d'allégeance au « Réfèrent » . Et qui est le Réfèrent ?
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; approches et analyses; corps; cours; discipline; europe; france; féminisme matérialiste; inégalités; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques